Determination of The Stages of Household Food Waste - Kaya, Dilek; Dilek, Serkan (Gümrük ve Ticaret Dergisi, 2024)
Although not emphasized much, food waste is one of the most important economic problems in the world and Türkiye. Food waste reduces households' welfare, makes it difficult for low-income groups to access food, and prevents the achievement of sustainable development goals. Despite waste being prohibited in Islam, food waste is common even in Muslim societies. In Türkiye, food waste is higher than in developed countries which are wealthier than it. Despite its importance, the theoretical aspect of food waste has not been sufficiently researched in economics. Food loss can occur during transportation from production to the household or by the household itself. Households reduce their welfare through food waste. Our study aims to determine the stages of food waste in households. As a result of the survey conducted for this purpose, it was revealed that food wastage occurs in three phases: planning, shopping, and consumption. Demographic variables such as age, education level, occupation, and income were found to also influence food wastage. It is believed that our study will pave the way for future research on food wastage and increase awareness about this issue.